2017
DOI: 10.1159/000484396
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin, an Activator of 1,25D3-MARRS Receptor/ERp57, Attenuates the Effects of TNF-α by Causing ADAM10-Dependent Ectodomain Shedding of TNF Receptor 1

Abstract: Background/Aims: We investigated how diosgenin, a steroidal sapogenin, has anti-tumor necrosis factor-α (TNF-α) effects in human aortic endothelial cells (HAECs). Methods: Tumor necrosis factor receptor 1 (TNFR1) was assessed by Western blot analysis. Intracellular Ca2+ was measured using Fluo-4 AM. Immunofluorescence staining was performed for a disintegrin and metalloprotease 10 (ADAM10). Results: Diosgenin (1 ∼ 100 nM) induced ectodomain shedding of TNFR1 within 30 min and attenuated TNF-α-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…We showed that overexpression of LRG1 in HUVECs resulted in the shedding of the TNFR1 ectodomain into conditioned medium, suggesting that the inhibitory effect of LRG1 on TNF-α-induced EC activation is mediated by post-translational modification of TNFR1. Structural analysis of the LRG1 protein sequence revealed an absence of known protease domains, but we showed that LRG1 increased the level of the active form of ADAM10, a sheddase with the known role of releasing soluble TNFR1 ectodomain in other contexts (Yang et al, 2015(Yang et al, , 2017. Consistent with this observation, the effect of LRG1 on TNFR1 shedding in HUVECs was partially abrogated in the presence of an ADAM10 inhibitor.…”
Section: Discussionsupporting
confidence: 78%
“…We showed that overexpression of LRG1 in HUVECs resulted in the shedding of the TNFR1 ectodomain into conditioned medium, suggesting that the inhibitory effect of LRG1 on TNF-α-induced EC activation is mediated by post-translational modification of TNFR1. Structural analysis of the LRG1 protein sequence revealed an absence of known protease domains, but we showed that LRG1 increased the level of the active form of ADAM10, a sheddase with the known role of releasing soluble TNFR1 ectodomain in other contexts (Yang et al, 2015(Yang et al, , 2017. Consistent with this observation, the effect of LRG1 on TNFR1 shedding in HUVECs was partially abrogated in the presence of an ADAM10 inhibitor.…”
Section: Discussionsupporting
confidence: 78%
“…Relt expression begins in pre-ameloblasts, continues through the secretory stage and, like Adam10 , abruptly ends as the ameloblasts enter the transition stage. Since ADAM10 is a sheddase that can cleave specific TNFRSF members and release them from the cell membrane 18,19 , we asked if ADAM10 can cleave RELT within its extracellular domain. To demonstrate rhADAM10 was proteolytically active, we incubated ADAM10 with its known substrate N-cadherin.…”
Section: Resultsmentioning
confidence: 99%
“…Serum proinflammatory factors were significantly elevated after reperfusion and diosgenin demonstrated anti-inflammatory properties [ 22 ], resulting in a decrease in the level of serum inflammatory markers TNF-α and IL-1β ( Figure 4A, 4B ). Lysosomal enzyme MPO is involved in diseases such as inflammation, vasculitis, and atherosclerosis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%